Bridging Public Perception and Law Enforcement in Police Accountability: Menjembatani Persepsi Publik dan Penegakan Hukum dalam Akuntabilitas Polisi - Nursukma, Ananda Wahyu; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2024)
General Background: Effective law enforcement is crucial for maintaining public trust and ensuring justice, particularly regarding police accountability in criminal acts. Specific Background: This research investigates public understanding and responses to law enforcement concerning police officers who fail to provide services. Despite the significance of reporting mechanisms, existing literature lacks comprehensive insights into the complexities and challenges involved in police reporting from the public’s perspective. Knowledge Gap: There is insufficient empirical evidence on how the public perceives and interacts with law enforcement processes, particularly in cases involving police misconduct. Aims: The study aims to analyze the dynamics of public reporting procedures related to police services and to assess the implications of these processes for improving the police system and public awareness of law enforcement. Results: Employing an empirical legal approach, the research utilizes direct observation and in-depth interviews with relevant stakeholders to gather data. The findings reveal that public perceptions of police accountability are influenced by various factors, including awareness of reporting procedures and perceived efficacy of law enforcement responses. Novelty: This research offers a unique perspective by integrating empirical data to elucidate the complexities surrounding police reporting and public engagement with law enforcement. Implications: The results contribute to a deeper understanding of the challenges within the police reporting system and highlight potential solutions for enhancing justice and order in society, thereby fostering a more transparent and effective law enforcement framework. Highlights: Public Perception: Examines public views on police accountability and reporting. Research Method: Employs empirical approaches through observations and stakeholder interviews. Improvement Solutions: Identifies challenges to enhance justice and public trust in policing. Keywords: police accountability, law enforcement, public reporting, empirical legal approach, justice system